THE INFLUENCE OF GREEN ACCOUNTING AND PROFITABILITY ON THE VALUE OF MINING AND MANUFACTURING COMPANIES REGISTERED ON THE JAKARTA ISLAMIC INDEX PERIOD 2018-2022 - Muhamad Defri Akbar; Rizki Rizki; Atika Atika (Politeknik Negeri Ambon, 2025)
Introduction: Company values aim to improve the welfare of owners, employees, and the environment. Some companies are not successful in increasing their company value. Green accounting and the size of profitability are among the factors influencing it. Green accounting carried out by companies can affect company value because every company is responsible for environmental damage resulting from its operational activities. Companies must also pay attention to their profitability because profitability is a significant part of company sustainability. This research aims to determine the effect of green accounting and profitability on the value of mining and manufacturing companies listed on the Jakarta Islamic Index for the period 2018-2022. Methods: This research uses descriptive statistical analysis methods, panel data regression, classical assumption tests, and hypothesis tests, which are processed using Eviews 12 with a descriptive approach. The data used is secondary data obtained from mining and manufacturing companies' annual reports and sustainability reports. Based on the criteria, a sample of 10 mining and manufacturing companies was obtained using purposive sampling techniques. Results: The research results show that partially green accounting does not affect company value with a probability of 0.5043 > 0.05. Profitability also does not affect company value with a probability of 0.3030 > 0.05. Meanwhile, green accounting and profitability have a significant influence on company value with the acquisition of prob. F-statistic is 0.000000 < 0.05. Keywords: Green Accounting, Profitability, Company Value